(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Fresh vegetables and fruits are the main sources of micro-nutrients and macro nutrients for health. Pesticides are mainly used to increase the yield. Pesticides are potentially toxic to humans and can have both acute and chronic health effects, depending on the nature of exposure and duration exposure and the quantity of exposure. This study was done to evaluate the efficacy of medicated vegetable wash comparison. Two samples of Medicated water were prepared according to the Kshara preparation of Ayurveda classics. In Samhitas various decontamination have been explained for various types of pollution. Two commonly used pesticides, Cypermethrin and chlorpyrofos were taken in this study. For this study organic vegetable ivy gourd (Coccinia grandis) were selected and treated with the pesticides as per QuEChERs method (quick, easy, cheap, effective, rugged and safe) method. The analysis was done GCMS/MS. The results depicted reduction of pesticide residue by medicated water decontamination process with distilled water. Although it varied in different in the two samples, overall medicated water 2 is having more effect on both pesticide residues over medicated water 1and distilled water.